Dampak Program Taman Edukasi Terhadap Peningkatan Minat Belajar Agama Dan Kemampuan Baca Al-Qur'an Anak-Anak Di Desa Baru - Matondang, Ahmad Barkah; Nasution, Mawaddah (EL-EMIR INSTITUTE, 2024)
The Taman Edukasi (Educational Garden) program implemented in Desa Baru, Pulau Rakyat District, Asahan Regency aimed to increase children's interest in religious learning and Qur'an reading ability. This study employed a qualitative approach with action research design, involving 60 elementary school-aged children. The program consisted of afternoon Qur'an teaching sessions, religious socialization in schools, and a children's Islamic festival. Results showed a significant increase in interest in religious learning and Qur'an reading ability, with 80% of children demonstrating improved Qur'an reading skills. The main challenge was maintaining consistency in children's participation. This research highlights the importance of interactive and enjoyable religious education programs in enhancing long-term religious literacy.